A comparative analysis of adaptive middleware architectures based on computational reflection and aspect oriented programming to support mobile computing applications - Costa, Celso Maciel da (2006)
Mobile computing applications are required to operate in environments in which the availability for resources and services may change significantly during system operation. As a result, mobile computing applications need to be capable of adapting to these changes to offer the best possible level of service to their users. However, traditional middleware is limited in its capability of adapting to environment changes and different users requirements. Computational Reflection and Aspect Oriented Programming paradigms have been used in the design and implementation of adaptive middleware architectures. In this paper, we propose two adaptive middleware architectures, one based on reflection and other based on aspects, which can be used to develop adaptive mobile applications. The reflection based architecture is compared to an aspect oriented based architecture from a quantitative perspective. The results suggest that middleware based on Aspect Oriented Programming can be used to build mobile adaptive applications that require less processor running time and more memory space than Computational Reflection while producing code that is easier to comprehend and modify.